Associated risks to abusive use of benzodiazepines: a literature review (Research, Society and Development, 2022)
Introduction: Benzodiazepines are a drugs class that have five main properties, anxiolytic, sedative, hypnotic, muscle relaxant and anticonvulsant. These substances were discovered in the 60's and since then their consumption has been growing more and more. Linked to this high consumption comes the inappropriate use that can bring significant consequences to the lives of users, such as cases of dependence, tolerance and abstinence. Objective: To expose the main health problems caused by the excessive use of benzodiazepines. Methodology: The study was developed through searches in the following databases: Google Scholar, Scielo, ANVISA, PubMed Central and CEBRID. Results: Researches were found that reported the main ills to the health of people who make incorrect and exacerbated use of benzodiazepines. Conclusion: It was possible to conclude that the continuous and exaggerated use of benzodiazepines affects not only the health of patients but also their daily lives. The use for a period of time longer than 26 days already exposes the user to the risk of developing withdrawal, tolerance or dependence, generating several impacts on the daily lives of users. In view of this, the importance of more individualized prescriptions and monitoring carried out by professionals is highlighted, as well as a reeducation of the population about self-medication and the undesirable effects caused by these drugs when used incorrectly.